Penerapan Arsitektur Neo Vernakuler Pada Desain Bentuk Pusat Pengolahan Kopi Di Kabupaten Enrekang - Aldi Septyadi Arsyad; Marwati, Marwati; AS, Zulkarnain (TIMPALAJA : Architecture Student Journals, 2023)
Coffee is one of the agricultural products included as Indonesia's superior product. Indonesian coffee is ranked fourth in the world in terms of its production output level. One of the most significant coffee production in South Sulawesi Province is located in Enrekang Regency. Arabica Coffee production in Enrekang Regency can reach above 1000 tons per year. With the existence of this Coffee Processing Center, it is also hoped to encourage economic growth and introduce the quality of the taste of Enrekang coffee beans so that they can become the leading commodity of South Sulawesi Province. By applying the concept of neo-vernacular architecture, it is intended that professionally managed coffee processing centers can prioritize modern management without leaving the local architectural aspects of Massenrempulu or Enrekang. The result of applying the vernacular concept to the processing building is an opening in the shape of the roof of the Enrekang house